Viruses associated with acute respiratory infection in a community‐based cohort of healthy New Zealand children. Issue 2 (7th May 2019) - Walker, Gregory J.; Stelzer‐Braid, Sacha; Shorter, Caroline; Honeywill, Claire; Wynn, Matthew; Willenborg, Christiana; Barnes, Phillipa; Kang, Janice; Pierse, Nevil; Crane, Julian; Howden‐Chapman, Philippa; Rawlinson, William D﻿.﻿
Abstract: Acute respiratory infections (ARIs) are a major cause of morbidity among children. Respiratory viruses are commonly detected in both symptomatic and asymptomatic periods. The rates of infection and community epidemiology of respiratory viruses in healthy children needs further definition to assist interpretation of molecular diagnostic assays in this population. Children otherwise healthy aged 1 to 8 years were prospectively enrolled in the study during two consecutive winters, when ARIs peak in New Zealand. Parents completed a daily symptom diary for 8 weeks, during which time they collected a nasal swab from the child for each clinical ARI episode. A further nasal swab was collected by research staff during a clinic visit at the conclusion of the study. All samples were tested for 15 respiratory viruses commonly causing ARI using molecular multiplex polymerase chain reaction assays. There were 575 ARIs identified from 301 children completing the study, at a rate of 1.04 per child‐month. Swabs collected during an ARI were positive for a respiratory virus in 76.8% (307 of 400), compared with 37.3% (79 of 212) of swabs collected during asymptomatic periods. The most common viruses detected were human rhinovirus, coronavirus, parainfluenza viruses, influenzavirus, respiratory syncytial virus, and human metapneumovirus. All of these were significantly more likely to be detected during ARIs than asymptomatic periods. Parent‐administered surveillance is a useful mechanism for understanding infectious disease in healthy children in the community. Interpretation of molecular diagnostic assays for viruses must be informed by understanding of local rates of asymptomatic infection by such viruses. Highlight: During winter, children experienced acute respiratory infections at a rate of 1.04/month. A virus was detected in 76.8% of acute respiratory infections. Specific viruses are more likely to be associated with respiratory symptoms.